Perspectives of significant improving of noise immunity in modern cellular communications - Bondarev, Andriy; Maksymiv, Ivan (Видавництво Львівської політехніки, 2012)
The simulation method of noise immunity improvement of radio signals with OQPSK and 8PSK at low signal-to-noise ratio is considered in this paper.
Keywords: 8PSK; OQPSK; signal-to-noise ratio; AWGN; Simulink; Matlab